1990
DOI: 10.1002/pros.2990160202
|View full text |Cite
|
Sign up to set email alerts
|

Effects of castration and androgens upon prostatic proteoglycans in rats

Abstract: In studies performed on male Wistar rats, castration induced atrophy of the prostate with a marked increase in the uronic acid content. The administration of testosterone propionate to castrated rats produced opposite effects. Fractionation of the glycosaminoglycans on cellulose microcolumns showed that the changes in uronic acid content in the dorsolateral lobes were due to variations in hyaluronic acid, chondroitin-4-sulfate, and dermatan sulfate, but in the ventral lobes, there were changes in all the chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
4

Year Published

1994
1994
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 7 publications
1
12
0
4
Order By: Relevance
“…There is also evidence that one or more serine proteases may be required, either to activate the enzyme proteolytically or to initiate the degradation of the nuclear matrii, to render the DNA more accessible to the endonucleases. Analysis of the fragments has shown that DNA fragmentation is probably a stepwise process, involving fragmentation at interrosette sites (generating DNA fragments larger than 300 kb), interloop sites (generating fragments of about 50 The secretory epithelial cells of the prostate interact with the basement membrane located between the stroma and the epithelium. Several lines of evidence suggest that the normal function of secretory epithelial cells is dependent on a complex interplay between the epithelium, the ECM and the underlying mesenchyme or stroma [2 51.…”
Section: Dna Fragmentationmentioning
confidence: 99%
“…There is also evidence that one or more serine proteases may be required, either to activate the enzyme proteolytically or to initiate the degradation of the nuclear matrii, to render the DNA more accessible to the endonucleases. Analysis of the fragments has shown that DNA fragmentation is probably a stepwise process, involving fragmentation at interrosette sites (generating DNA fragments larger than 300 kb), interloop sites (generating fragments of about 50 The secretory epithelial cells of the prostate interact with the basement membrane located between the stroma and the epithelium. Several lines of evidence suggest that the normal function of secretory epithelial cells is dependent on a complex interplay between the epithelium, the ECM and the underlying mesenchyme or stroma [2 51.…”
Section: Dna Fragmentationmentioning
confidence: 99%
“…The secretory cells of the prostate interact with the basement membrane located between the stroma and epithelium. The extracellular matrix contains a number of components including fibronectin, collagen, laminin, vitronectin, heparan sulfate, and chondroitin sulfate (Kofoed et al 1990;Paulsson 1992). These components are known to interact with their cognate receptors, many of which are members of the integrin superfamily (Hynes 1992;Damsky and Werb 1992;Juliano and Haskil 1993).…”
Section: Role Of the Extracellular Matrix Proteases And Growthmentioning
confidence: 99%
“…The prostatic stroma is rich in extracellular matrix (ECM) elements such as collagen Wbers (Vilamaior et al 2000), proteoglycans (Kofoed et al 1990), laminin (Carvalho and Line 1996), Wbronectin and elastin (Carvalho et al 1997). In addition to a structural role, the ECM and related molecules have been recognized as key regulatory components during developmental morphogenesis and cell diVerentiation of many branched organs (Timpl 1989;Gilbert 2006).…”
Section: Introductionmentioning
confidence: 98%